Analisis Analisis Kualitas Mutu Produksi Bubuk Kakao di Pusat Penelitian Kopi dan Kakao Indonesia - Dwicahyo, Agung; Mulya Santosa, Kresna; Rani Nurfadila, Agustin (Politeknik Negeri Jember, 2024)
Cocoa is one of the agricultural commodities that has the potential to be developed in Indonesia. Cocoa beans can be processed into processed food products with high selling value. Processed cocoa products include chocolate bars, cocoa butter and cocoa powder. Several processing stages are required to process cocoa into food products, including secondary and tertiary processing. Cocoa powder is one of the processed cocoa products that is in great demand by consumers. The use of cocoa powder as a substitute for processed food makes the process of processing cocoa powder very interesting for research. One of the factors that influences the quality of cocoa powder is the level of fineness of the cocoa powder.